تطبيق الكفاءة المهنية لدى مدرسي اللغة العربية بمدرسة أخوة المتوسطة الإسلامية المتكاملة ببنجرماسين )دراسة وصفية( - Nurhayati, Risa; Muradi, Ahmad; Mubarak, Faisal (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2021)
This research discusses the application of the professional competence of the Arabic language teachers at the Ukhuwah Integrated Islamic Junior High School, Banjarmasin. The discussion in this research is carried out by suggesting the importance of the role of the teachers in the process of being successful in order to enhance the quality of education. Therefore, the teachers must pay close attention to their competencies before engaging to the learning process. The most important factors in the success of a learning is the teacher, it have been known that the teacher is the most dominant factors in the success of a learning. This study uses a descriptive method with a qualitative approach. The data is collected by using the observation, interviews, and documentation. The subjects of this research were the Arabic teachers. The results showed: The professional competence of the Arabic teachers in the Ukhuwah Integrated Islamic Junior High School Banjarmasin is meets the requirements of all aspects needed such as mastering the scientific substances related to the field of study, understanding teaching materials; being able to design well the learning programs in accordance with what is in the school curriculum, understanding the structure, concepts and scientific methods that are shading or coherent with teaching materials, developing professionalism in a sustainable manner by taking action of reflection and utilizing the information and communication technology for self-development